Is ACL reconstruction a prerequisite for the patients having recreational sporting activities? - Emrah Kovalak; Tolga Atay; Cem Çetin; İ. Meltem Atay; Mustafa Onur Serbest (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: Whether surgical or conservative treatment is more effective in allowing patients to return to physical activity after anterior cruciate ligament (ACL) injury is controversial. We sought to compare mid-term outcome measures between isolated ACL tear patients who underwent reconstruction followed by closed kinetic chain exercises and those who underwent neuromuscular training only. Methods: We retrospectively evaluated patients with ACL tears who underwent post-surgery CKC strength training after ACL reconstruction (Group A), and patients who only underwent neuromuscular training (Group B) with a minimum follow-up time of 5 years. Surgical techniques, rehabilitation, assessment of subjective knee function, one-leg hop test, assessment of joint position sense, muscle strength, and the health profile of the patient were evaluated. Results: Overall, 43 patients were included in Group A (mean age, 32.56 ± 4.89; Tegner activity scale, 5) and 39 patients in Group B (31.67 ± 7.27; 5). Patients in both groups returned to their regular physical activity level after a similar time frame (Group A: average, 12 months; Group B, average, 13.4 months). The mean Lysholm knee score was 88.52 ± 7.65 in Group A and 86.21 ± 13.72 in Group B. Mean distances for the one-leg hop test for Group A were 135.21 ± 31.66 and 145.36 ± 42.10 mm in the reconstructed and uninjured knees, respectively. In Group B, the mean hop distances were 132.47 ± 28.13 and 147.89 ± 21.45 mm in the rehabilitated and uninjured knees, respectively. No statistical difference was observed between the groups for any of the parameters evaluated, including assessment of subjective knee function, one-leg hop test, assessment of joint position sense, muscle strength, and the health profile. Conclusion: Our data suggest that early surgical reconstruction may not be a prerequisite to returning to recreational physical activities after injury in patients with ACL tears. Level of evidence: Level IV, therapeutic study. Keywords: Anterior cruciate ligament, Anterior cruciate ligament reconstruction, Functional performance tests, Knee joint, Neuromuscular joint facilitation, Proprioception